2020
DOI: 10.1002/jpln.201900353
|View full text |Cite
|
Sign up to set email alerts
|

Modern wheat cultivars have greater root nitrogen uptake efficiency than old cultivars

Abstract: The availability of nitrogen (N) contained in crop residues for a following crop may vary with cultivar, depending on root traits and the interaction between roots and soil. We used a pot experiment to investigate the effects of six spring wheat (Triticum aestivum L.) cultivars (three old varieties introduced before mid last century and three modern varieties) and N fertilization on the ability of wheat to acquire N from maize (Zea mays L.) straw added to soil. Wheat was grown in a soil where 15N‐labeled maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
2
19
4
Order By: Relevance
“…The response of wheat growth to soil nutrient levels has received much attention. Many studies have shown that N is a major limiting factor in crop production, with a positive relationship between wheat yield and N amount [63][64][65]. Our results are consistent with these studies, and we found that aboveground biomass and yield increased with increasing N. Such effects of N on wheat yield are reasonable, because increasing N levels significantly increase the grain count, the number of spikes, and the thousand-grain weight [66].…”
Section: Discussionsupporting
confidence: 92%
“…The response of wheat growth to soil nutrient levels has received much attention. Many studies have shown that N is a major limiting factor in crop production, with a positive relationship between wheat yield and N amount [63][64][65]. Our results are consistent with these studies, and we found that aboveground biomass and yield increased with increasing N. Such effects of N on wheat yield are reasonable, because increasing N levels significantly increase the grain count, the number of spikes, and the thousand-grain weight [66].…”
Section: Discussionsupporting
confidence: 92%
“…Gaju et al [14] also reported great variations among wheat genotypes ranging from 36% for "W300" to 53% for "Cordiale," and higher HI under low N (46%) compared with optimum N (43%), which support the present findings. Corroborating the current observation, Zhang et al [37] also reported that HI did not differ between N fertilized and unfertilized treatments but significantly varied among wheat cultivars that contrasted in N efficiency. In this study, HI showed weak correlation with grain yield under both low and optimum N (data not shown) as contrasted to Gaju et al [14], who attained positive linear relationships among genotypes between HI and grain yield under high N and low N conditions.…”
Section: Discussionsupporting
confidence: 85%
“…A general understanding among Swedish growers is that old wheat varieties have a strong root growth, which contributes to their good performance during dry conditions, although scientific evidence for such a statement is lacking. However, in a recent study, a larger root system was observed in old wheat varieties than in modern wheat [ 34 ]. Furthermore, this large-to-small change in root biomass from old to modern wheat has been confirmed by several studies [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%